ANALISIS KINERJA PENGOPERASIAN DAN PELAYANAN BUS ANTAR KOTA ANTAR PROVINSI (AKAP) (STUDI KASUS PADA BIRO PERJALANAN UMUM (BPU) “ROSALIAN INDAH”) - Dwi Widiyanti (Sekretariat Badan Kebijakan Transportasi, Formerly by Puslitbang Transportasi Laut, Sungai, Danau, dan Penyeberangan, 2016)
ABSTRACTThe purpose of this study is to determine the performance of operation, conformity with minimum service standards, and the strategies that can be done to make improvements safety services on AKAP buses of BPU Rosalia Indah. The design study is a survey research design, the method of collecting data or information with instrument field surveys and interview. With data analysis External Factors Strategy (EFS) and Internal Factor Strategy (IFS), the results showed that the BPU Rosalia Indah 53% already implementing SPM and 92% the comfort according of PM 29 in 2015. The company already 92% implementing rules in PM 26 2015 about Road Safety Standard Operating AKAP bus. Besides the internal conditions of operation AKAP bus